Dinamika Perbedaan Pendapat Ulama Terkait ketentuan al¬-Maur ṹṣ atau Harta bersama bagi Janda dan Duda Setelah Formulasi Kompilasi Hukum Islam. - Muhammad Fadhlan Is (Institut Agama Islam Negeri Metro, 2023)
One of the important studies in Islamic family law is the provision of inheritance. Inheritance provisions are often a source of disputes within the family, especially in determining who is entitled to receive an inheritance. One form of progress in Islamic law in Indonesia is the formulation of the Compilation of Islamic Law. Article 97 of the Islamic Law Compilation stipulates that the share of inheritance for widows and widowers states that